ANALYSIS OF LEARNING AGILITY IN THE PERFORMANCE OF ACHIEVEMENT TEACHERS IN YOGYAKARTA - Ayu Meryka Santoso; Yuzarion Yuzarion (PEDAGOGIK : JURNAL PENDIDIKAN, 2021)
This study aims to analyze learning agility in the performance of outstanding teachers in Yogyakarta from the aspects of people agility, mental agility, change agility, and result agility. The method used is descriptive with a qualitative approach. The sampling technique used was purposive sampling with the following criteria: 1) teacher; 2) aged 27-55 years; 3) have achievements; 4) still active in teaching activities. The sample used is a typical case sample, where the special research subjects are outstanding teachers at SMU Negeri 8 Yogyakarta. Collecting data using structured interviews, then described and identified into several themes. The results showed that outstanding teachers had high learning agility at work. They perform maximum work performance, can take lessons from work experience, and respond to changes with full awareness and enthusiasm for learning to improve skills, knowledge, and self-competence. Social support and goal orientation are needed in building learning agility in teachers to develop. Learning agility plays an important role in improving the quality of teacher performance, so that, the education quality and the learning spirit can continue to be improved and becomes an inspiration for the young generation.